Pengaruh Work-Life Balance Dan Work Engagement Terhadap Kepuasan Kerja Implikasinya Terhadap Kinerja Amil (Studi Pada Laznas Baitul Maal Hidayatullah Jakarta) - Humaini Humaini; Rachman Upe; Abbas Thaha (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2024)
One of the keys to the change and progress of philanthropic institutions lies in human resources and digital infrastructure based on technology. This research intends to look at the impact of Work-life Balance and work engagement on Job Satisfaction and its implications on Amil's performance. This scientific work uses a quantitative approach, this research was carried out on all amil with a sample of 52 amil using the Slovin formula. The sampling method uses a probability sampling approach with the Simple Random Sampling technique. The analysis technique of this study uses Partial Least Square (PLS) and the F SPSS test. From the results of the hypothesis test, it is known that 1. Work-life balance has a positive and significant effect on job satisfaction. Second, Work Engagement has a positive and significant influence on job satisfaction. 3 Work-life balance and work engagement together affect job satisfaction. The 4th Work-life Balance has a positive and significant effect on performance. 5. Work engagement has a positive and significant effect on Performance. 6 Job satisfaction affects the performance of the amil. 7. Work life balance, work engagement affects performance simultaneously through job satisfaction. This research can be used as a reference to improve and maintain work-life balance, work engagement, job satisfaction, and performance.